2019
DOI: 10.1021/jacs.9b07267
|View full text |Cite
|
Sign up to set email alerts
|

Para-Selective C–H Borylation of Common Arene Building Blocks Enabled by Ion-Pairing with a Bulky Countercation

Abstract: The selective functionalization of C–H bonds at the arene para position is highly challenging using transition metal catalysis. Iridium-catalyzed borylation has emerged as a leading technique for arene functionalization, but there are only a handful of strategies for para-selective borylation, which operate on specific substrate classes and use bespoke ligands or catalysts. We describe a remarkably general protocol which results in para-selectivity on some of the most common arene building blocks (anilines, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 53 publications
0
65
0
3
Order By: Relevance
“…[87] Enhanced para selectivity is similarly observed in the borylation of sulfamate and sulfate salts in which a tetraalkylammonium counterion shields nominally active meta CÀH sites (Scheme 7 b,c). [88,89] In a ligand-based approach, the use of the bulky phosphine ligand L3 creates a flexible reaction pocket at the active catalyst which inhibits the access to meta aryl CÀH bonds (Scheme 7 d). [90,91] Finally, whilst most ligands are based on a simple bipyridine template, Smith and Maleczka have excitingly shown that alternative motifs have considerable potential to enhance selectivity, with hindered electron-rich ligands dipyridylmethane (dpm, L4) and 4,4'-bis(dimethylamino)-2,2'dipyridyl)methane (dmadpm, L5) favouring steric control, and unhindered electron-poor ligands 2,2'-bis-2-oxazoline (bozo, L6) and 2,2'-bis[(4S)-4-benzyl-2-oxazoline] (bnbozo, L7), favouring greater degrees of electronic control (Scheme 7 e).…”
Section: Aromatic C à H Borylationmentioning
confidence: 99%
See 1 more Smart Citation
“…[87] Enhanced para selectivity is similarly observed in the borylation of sulfamate and sulfate salts in which a tetraalkylammonium counterion shields nominally active meta CÀH sites (Scheme 7 b,c). [88,89] In a ligand-based approach, the use of the bulky phosphine ligand L3 creates a flexible reaction pocket at the active catalyst which inhibits the access to meta aryl CÀH bonds (Scheme 7 d). [90,91] Finally, whilst most ligands are based on a simple bipyridine template, Smith and Maleczka have excitingly shown that alternative motifs have considerable potential to enhance selectivity, with hindered electron-rich ligands dipyridylmethane (dpm, L4) and 4,4'-bis(dimethylamino)-2,2'dipyridyl)methane (dmadpm, L5) favouring steric control, and unhindered electron-poor ligands 2,2'-bis-2-oxazoline (bozo, L6) and 2,2'-bis[(4S)-4-benzyl-2-oxazoline] (bnbozo, L7), favouring greater degrees of electronic control (Scheme 7 e).…”
Section: Aromatic C à H Borylationmentioning
confidence: 99%
“… [87] Enhanced para selectivity is similarly observed in the borylation of sulfamate and sulfate salts in which a tetraalkylammonium counterion shields nominally active meta C−H sites (Scheme 7 b,c). [88, 89] In a ligand‐based approach, the use of the bulky phosphine ligand L3 creates a flexible reaction pocket at the active catalyst which inhibits the access to meta aryl C−H bonds (Scheme 7 d). [90, 91] …”
Section: Aromatic C−h Borylationmentioning
confidence: 99%
“… [87] Erhöhte para ‐Selektivität kann auch bei der Borylierung von Sulfamaten und Sulfaten beobachtet werden, wo ein Tetraalkylammonium‐Gegenion die nominal aktive meta ‐C‐H‐Bindung abschirmt (Schema 7 b,c). [88, 89] Bei einem Ansatz auf Ligandenbasis wird durch die Verwendung eines sperrigen Phosphanliganden L3 eine flexible Reaktionstasche am aktiven Katalysator erzeugt, die den Zugang zur meta ‐C‐H‐Bindung inhibiert (Schema 7 d). [90, 91] …”
Section: Aromatische C‐h‐borylierungunclassified
“…[87] Erhçhte para-Selektivitätk ann auch bei der Borylierung von Sulfamaten und Sulfaten beobachtet werden, wo ein Tetraalkylammonium-Gegenion die nominal aktive meta-C-H-Bindung abschirmt (Schema 7b,c). [88,89] Bei einem Ansatz auf Ligandenbasis wird durch die Verwendung eines sperrigen Phosphanliganden L3 eine flexible Reaktionstasche am aktiven Katalysator erzeugt, die den Zugang zur meta-C-H-Bindung inhibiert (Schema 7d). [90,91] Während die meisten Liganden auf einfachen Bipyridin-Vorlagen beruhen, haben Smith und Maleczka außerdem gezeigt, dass alternative Motive ein beträchtliches Potenzial haben, die Selektivitätz ue rhçhen, wobei die gehinderten elektronenreichen Liganden Dipyridylmethan (dpm, L4)und 4,4'-Bis(dimethylamino)2,2'-dipyridyl)methan (dmadpm, L5) eine sterische Kontrolle begünstigen und die ungehinderten elektronenarmen Liganden 2,2'-Bis-2-oxazolin (bozo, L6) und 2,2'-Bis[(4S)-4-Benzyl-2-oxazolin] (bnbozo, L7)e in hçheres Maß an elektronischer Kontrolle begünstigen (Schema 7e).…”
Section: Ir-katalysierte C-h-borylierung Von Arenenunclassified
“…Methods to accomplish a lipophilic cation-exchange of highly polar sulfated molecules include the process route to Avibactam reported by Ball et al 12 . Recent work by Montero Bastidas et al 21 , and Mihai et al 22 have shown the importance of routes to sulfated molecules with a sterically bulky tetrabutylammonium cation for iridium catalysed para -selective C–H borylations. An alternate approach is to design an all-in-one reagent with a sulfating agent combined with a lipophilic counterion, such as our own work 19 , 20 and the work of Kowalska et al 23 .…”
Section: Introductionmentioning
confidence: 99%